Generalized Modules for Membrane Antigens as Carrier for Polysaccharides: Impact of Sugar Length, Density, and Attachment Site on the Immune Response Elicited in Animal Models - Micoli, Francesca; Alfini, Renzo; Di Benedetto, Roberta; Necchi, Francesca; Schiavo, Fabiola; Mancini, Francesca; Carducci, Martina; Oldrini, Davide; Pitirollo, Olimpia; Gasperini, Gianmarco; Balocchi, Cristiana; Bechi, Nicoletta; et al. (Frontiers in Immunology, 2021)
Nanoparticle systems are being explored for the display of carbohydrate antigens, characterized by multimeric presentation of glycan epitopes and special chemico-physical properties of nano-sized particles. Among them, outer membrane vesicles (OMVs) are receiving great attention, combining antigen presentation with the immunopotentiator effect of the Toll-like receptor agonists naturally present on these systems. In this context, we are testing Generalized Modules for Membrane Antigens (GMMA), OMVs naturally released from Gram-negative bacteria mutated to increase blebbing, as carrier for polysaccharides. Here, we investigated the impact of saccharide length, density, and attachment site on the immune response elicited by GMMA in animal models, using a variety of structurally diverse polysaccharides from different pathogens (i.e., Neisseria meningitidis serogroup A and C, Haemophilus influenzae type b, and streptococcus Group A Carbohydrate and Salmonella Typhi Vi). Anti-polysaccharide immune response was not affected by the number of saccharides per GMMA particle. However, lower saccharide loading can better preserve the immunogenicity of GMMA as antigen. In contrast, saccharide length needs to be optimized for each specific antigen. Interestingly, GMMA conjugates induced strong functional immune response even when the polysaccharides were linked to sugars on GMMA. We also verified that GMMA conjugates elicit a T-dependent humoral immune response to polysaccharides that is strictly dependent on the nature of the polysaccharide. The results obtained are important to design novel glycoconjugate vaccines using GMMA as carrier and support the development of multicomponent glycoconjugate vaccines where GMMA can play the dual role of carrier and antigen. In addition, this work provides significant insights into the mechanism of action of glycoconjugates.